1995
DOI: 10.1016/0014-5793(95)00085-n
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibitors augment the production of pro‐matrix metalloproteinase 9 (progelatinase B) in rabbit articular chondrocytes

Abstract: Matrix metalloproteinase 9 (MMP-91gelatinase B) has recently been proposed to participate in the destruction of articular cartilage. Here, we report that interleukin 1 ([L-l) enhances the production of the precursor of MMP-9 in rabbit articular chondrocytes in primary culture, and this IL-l-mediated production of proMMP-9 is greatly augmented by cyclooxygenase inhibitors such as diclofenac and indomethacin, whereas the constitutive production of proMMP-2 (progelatinase A) is not modulated by IL-1 and/or cycloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…MMP-9 has been implicated in cellular migration and invasion in patients with such conditions as inflammation, tumor invasion, and metastasis. In addition, recent studies of this proteinase in the skeleton suggest that MMP-9 could exist in matrix vesicles (27), digest cartilage proteoglycans (28,29), and play important roles in chondrocyte apoptosis (30) and osteoclastic bone resorption (31)(32)(33). MMP-9 can also be produced by activated osteoclasts (34).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 has been implicated in cellular migration and invasion in patients with such conditions as inflammation, tumor invasion, and metastasis. In addition, recent studies of this proteinase in the skeleton suggest that MMP-9 could exist in matrix vesicles (27), digest cartilage proteoglycans (28,29), and play important roles in chondrocyte apoptosis (30) and osteoclastic bone resorption (31)(32)(33). MMP-9 can also be produced by activated osteoclasts (34).…”
Section: Discussionmentioning
confidence: 99%
“…and other matrix molecules (22,34,54,55). Normal human and rabbit articular cartilage and cultured chondrocytes express little or undctectable levels of MMP-9 under basal conditions, but the gene is induced by treatment with inflammatory cytokines such as interleukin-la (IL-la) (32,35,43,51,57,64). In osteoarthritis, the expression of MMP-9 mRNA and protein is increased in articular cartilage and isolated chondrocytes (24.51.71).…”
mentioning
confidence: 99%
“…These results are in agreement with those of others. [24][25][26] Studies by Ito et al have reported that diclofenac has a positive effect on the inhibition of cartilage metabolism. 26) B. platyphylla inhibited MMP-3 and MMP-13 mRNA and protein expression, as well as their activity, in articular cartilage explants (Figs.…”
Section: Discussionmentioning
confidence: 99%